Distribuição espacial e estratificação vertical de flebotomíneos (Diptera: Psychodidae) em matas ciliares no baixo curso do Rio Munim. - MORAES, Jorge Luiz Pinto (2012)
Theoretical basis Phlebotomines sand flies are important insect for two aspects: first they use vertebrates as a food source and thus may be indicators of threatened areas, and second, because they are hematophagous and transmitters of Leishmania protozoa that cause leishmaniasis. In the world there are records of the occurrence of insects in tropical forests as well as in other areas. Six genera include species of sand fly, Phlebotomus and Sergentomyia are distributed in the Old World and Lutzomyia, Hertigia,Warileya e Brumptomyia in the Americas. There are about 800 identified species in the world, about 480 in the Americas, 229 in Brazil and 91 in the state of Maranhão. Sandflies are primarily wild, though some species are already adapted to the human environment, due to various human activities, which culminate in the reduction of natural areas, one of the main threats to biodiversity. In Maranhão, studies on phlebotomine occurred in areas with endemic leishmaniasis, specifically in rural areas, however in the wild have been conducted in forest fragments in metropolitan St. Louis and only analyzing the horizontal distribution of sand flies, it does not address the vertical stratification. The work resulted in two articles: The first was to identify the phlebotomine fauna composition in six areas of riparian forest in lower reaches of the Munim River, northern state of Maranhão. In this, the fauna was diverse and it was found in 2106 specimens distributed in 21 species belonging to two genera, Lutzomyia e Brumpyomyia. L. flaviscutellata, L. infraspinosa, L. antunesi, L. wellcomei, L. sordellii and L. furcata were the most abundant. Fourteen species occurred in two seasons, rainy and dry seasons, only four in the rainy season and three during the dry season. Seven species were considered constant, occurring in more than 50% of the collections; six were accessories, occurring between 25% and 50% of the collections, and eight were accidental, present in less than 25% of coletas. O second study examined the vertical stratification of phlebotomine sand flies in two riparian forest in the same region. We captured 784 specimens of 16 species belonging to the genera Lutzomyia e Brumpyomyia. The most abundant species were L.antunesi, L. wellcomei and L. infraspinosa. The number of males was higher (51.9%). The richness was similar between the areas in Girimico 13 species, compared to 12 in Porto Seguro. The abundance was higher in Girimico with (62.6%) and Porto Seguro (37.4%). The number of species in the two forests was higher in sub-canopy, 12 and 11 in Girimico in Porto Seguro. In the canopy were identified 10 species in Girimico and 6 species in Porto Seguro. The most abundant were L. wellcomei, L. antunesi and L. infraspinosa in Girimico no sub-canopy. In Porto Seguro L. antunesi was also the most representative of the substrate. Eleven species were found in two seasons, only three in the rainy and just two dry season. Phebotomines sand flies were more abundant in the rainy season (68.2%), highlighting the month in January (45.4%) in the dry season, December stood out with 12.2%. Five species were considered constant, four accessory and seven accidental. Phlebotomine sand flies were more abundant in the rainy season. Eleven species were found in two seasons, only three in the rainy and two in dry seasons. Among the species identified six were considered constant, four accessory and six accidental.